2023
DOI: 10.3390/cells12060831
|View full text |Cite
|
Sign up to set email alerts
|

CircXPO1 Promotes Glioblastoma Malignancy by Sponging miR-7-5p

Abstract: Mounting evidence suggests that circular RNAs play important roles in the development and progression of cancers. However, their function in glioblastomas (GBM) is still unclear. By circRNA array analysis, we found that circXPO1 (hsa_circ_102737) was significantly upregulated in GBM, and qPCR analysis verified that the circXPO1 expression level was increased in both GBM tissues and cell lines. Functional studies demonstrated that the knockdown of circXPO1 in GBM cell lines repressed cell proliferation and migr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 48 publications
0
0
0
Order By: Relevance
“…39 Besides, the results of the rescue experiments revealed that miR-488-3p inhibition or MEF2C upregulation reversed the inhibitory impact of circVCAN silencing on glioma cell growth as well as metastasis, implicating that circVCAN boosted the malignant behaviors of glioma cells through regulating the miR-488-3p/MEF2C axis, which was in line with previous reports. 40,41 MEF2C, a member of the myocyte enhancer factor 2 family, is a transcription factor essential for the development of organs such as heart 42 and nervous system. 43 The function of MEF2C in cancer is specific to the environment, serving as an activator of tumorigenesis in T-cell acute lymphoblastic leukemia, 44 driving chemotherapy resistance in hepatocellular carcinoma cells, 45 or inhibiting tumor growth in soft-tissue sarcomas.…”
Section: Discussionmentioning
confidence: 99%
“…39 Besides, the results of the rescue experiments revealed that miR-488-3p inhibition or MEF2C upregulation reversed the inhibitory impact of circVCAN silencing on glioma cell growth as well as metastasis, implicating that circVCAN boosted the malignant behaviors of glioma cells through regulating the miR-488-3p/MEF2C axis, which was in line with previous reports. 40,41 MEF2C, a member of the myocyte enhancer factor 2 family, is a transcription factor essential for the development of organs such as heart 42 and nervous system. 43 The function of MEF2C in cancer is specific to the environment, serving as an activator of tumorigenesis in T-cell acute lymphoblastic leukemia, 44 driving chemotherapy resistance in hepatocellular carcinoma cells, 45 or inhibiting tumor growth in soft-tissue sarcomas.…”
Section: Discussionmentioning
confidence: 99%